2023
DOI: 10.3389/fmed.2023.1091246
|View full text |Cite
|
Sign up to set email alerts
|

Frailty modifies the effect of polypharmacy and multimorbidity on the risk of death among nursing home residents: Results from the SHELTER study

Abstract: BackgroundFrailty, disability, and polypharmacy are prevalent in nursing home (NH) residents, often co-occurring with multimorbidity. There may be a complex interplay among them in terms of outcomes such as mortality. Aims of the study were to (i) assess whether nursing home residents with polypharmacy (5–9 medications) or hyperpolypharmacy (≥10 drugs), have an increased risk of death and (ii) whether any association is modified by the co-presence of frailty or disability.MethodsCohort study with longitudinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
0
2
0
1
Order By: Relevance
“…Other studies have also shown that among elderly individuals with high prevalence of medication use, most medications belonged to a very restricted number of ATC classes [22][23][24][25][26] . Furthermore, it has been reported that among elderly individuals (residents of nursing facilities) the association of polypharmacy with mortality risk may be modified by other health conditions such as frailty, and that risk of death was increased mostly by frailty and disability, whereas (hyper-)polypharmacy was associated with higher risk of death only among non-frail study participants 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also shown that among elderly individuals with high prevalence of medication use, most medications belonged to a very restricted number of ATC classes [22][23][24][25][26] . Furthermore, it has been reported that among elderly individuals (residents of nursing facilities) the association of polypharmacy with mortality risk may be modified by other health conditions such as frailty, and that risk of death was increased mostly by frailty and disability, whereas (hyper-)polypharmacy was associated with higher risk of death only among non-frail study participants 27 .…”
Section: Discussionmentioning
confidence: 99%
“…La intervención sobre la prescripción adecuada y el tratamiento de síndromes geriátricos y comorbilidades es básico. Los ancianos frágiles generalmente se asocian a un mayor número de fármacos [ 39 ], con mayor riesgo de efectos secundarios por sus interacciones. La prescripción farmacológica tiene que ser cuidadosa, evitando medicamentos inapropiados y valorando bien su beneficio.…”
Section: Manejo De La Fragilidad La Función Como Marcador De Objetivo...unclassified
“…In particular, multimorbidity, as defined by the co-presence of two or more chronic conditions (e.g., heart failure/disease, stroke, diabetes, cancer, dementia, depression), is indeed prevalent in nursing home residents, and often it is, in turn, co-occurring with frailty, disability and polypharmacy. Moreover, older residents with multimorbidity and with hyper-polypharmacy have, respectively, a 35% and a 29% increased risk of mortality when compared to those not experiencing these conditions [92]. These older people need appropriate healthcare services, and nursing homes, however, representing a possible care solution in their daily living [93,94].…”
Section: Health and Functional Statusmentioning
confidence: 99%